Community structure characteristics of medium- and small-sized soil faunas in typical artificial plantations in the upper reaches of Yangtze River - PENG Caiyun; WANG Ge; ZHAO Bo; LIAO Xingyan; ZHANG Jian; XIAO Jiujin; MU Chenjun (浙江大学学报. 农业与生命科学版, 2019)
To understand the characteristics of the soil fauna community structure in the typical artificial plantation system in the hilly region of the upper Yangtze River, in October 2015, Pinus massoniana (PM), Eucalyptus grandis (EG), Toona ciliata (TC), Bambusa rigida (BR) systems were selected as research objects, and the farm land (FL) system as a control. The structure of medium- and small-sized soil faunas was investigated by Tullgren and Baermann methods, respectively. A total of 4 444 individuals of soil faunas, belonging to 5 phyla, 12 classes, 22 orders and 83 kinds were collected. The average density of soil faunas achieved very significant levels among the five sample plots (F=78.478, P=0.000), and the group number of soil faunas had significant differences (F=4.810, P=0.020). The vertical distribution of soil faunas in all the soil layers decreased with the deepening of the soil layer, and showed the characteristics of the surface accumulation. Herbivorous, omnivorous and predatory soil animals in the BR accounted for the highest proportion, and saprophagous soil animals in the FL reached to the highest proportion. The diversity index, evenness index, richness index and density-group index of soil animals were the highest in the BR, and the dominance index was the highest in the FL. Except for the density-group index (F=2.702, P=0.092), the differences of other indexes reached highly significant levels (P<0.01). The similarity between the artificial plantation plots and FL was medium unsimilarity (except for the EG), and the similarity among the artificial plantation systems was moderate (except for the FL). The above results show that the soil animal community structure and diversity indexes in different plantations differ from each other, and there is higher diversity of soil faunas in the BR.